Teknik RAPD (Random Applied Polymorphic DNA) untuk Analisis Keanekaragaman Genetik pada Tanaman Ciplukan (Physalis angulata L.) di Kabupaten Labuhan Batu Utara - Yusvita, Diana; Idami, Zahratul (Bioscientist : Jurnal Ilmiah Biologi, 2024)
The ciplukan plant (Physalisangulata L.) can be used as traditional medicine, but so far people only know that this plant can only be used for the fruit. This research aims to determine the results of RAPD primary analysis which can produce polymorphic bands in Ciplukan Plants (Physalisangulata L.) in North Labuhan Batu Regency using different primers. This research is a quantitative research. Sampling was carried out in Bondar Village and Simpang Tiga Village, Kualuh Leidong District, North Labuhan Batu Regency. Then continued with molecular analysis at the Genetics Laboratory, Faculty of Science and Technology, North Sumatra State Islamic University, Medan. The results of RAPD (Random Applied Polymorphism DNA) analysis of ciplukan plants in North Labuhan Batu district using six different primers, namely the length of the nucleotides in the amplified DNA fragments, are shown in primers OPA-2 & OPA-3 are 600bp-3000bp, while OPA-5, OPA-7, OPD -11, & OPD-13 are 500bp-3000bp with different nucleotide sequences. The differences in the length and number of nucleotide sequences in ciplukan plants are caused by the plants used coming from different locations and several factors such as the environment, population size, natural conditions, reproductive methods and natural selection.